REPRESENTASI NILAI-NILAI PENDIDIKAN KARAKTER PADA KARTUN FAWWAZ WA NURAH: SEMIOTIKA CHARLES PEIRCE - Aqila Fikriya Hamidah; Rohanda Rohanda; Rifqi Muhammad Firdaus (Afshaha: Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to analyze the representation of character education values in the animated series Fawwaz wa Nurah using Charles Sanders Peirce’s semiotic approach. This fusha Arabic cartoon portrays the daily lives of two Muslim children and is rich in character education values such as honesty, responsibility, hard work, discipline, peace-loving attitudes, social awareness, tolerance, and creativity. The study employs a qualitative descriptive method, using viewing, observing, and note-taking techniques on selected episodes. The analysis is conducted by identifying visual and verbal signs, which are then interpreted through Peirce’s three semiotic elements: representamen, object, and interpretant. The findings reveal that Fawwaz wa Nurah consistently conveys character education messages through symbolic representations that are easily understood by children. These semiotic processes demonstrate how values are constructed and internalized in subtle yet effective ways. Thus, the cartoon not only entertains but also serves as an educational medium that fosters ethical awareness and positive character development in children from an early age.